Investigating the correlates and predictors of job satisfaction among Malaysian academic librarians - Karim, N.H.A. (2008)
This study employs a global measure for job satisfaction on the following ten work and worker related variables: affective commitment, continuance commitment, job involvement, job autonomy, job feedback, role clarity, role conflict, age, organizational tenure and job tenure. A survey was conducted to investigate how much of the variance in job satisfaction can collectively be explained by these variables in a Malaysian academic library setting. The survey was administered on 279 academic librarians from eight university libraries in West Malaysia. Findings were based on the responses from 139 usable questionnaires. The findings revealed that only six of the ten work and worker related variables were significantly correlated with job satisfaction: affective commitment, job autonomy, job performance feedback, role conflict, role clarity and organizational tenure. Findings also revealed that of these six correlates, only two have predictive relationship with job satisfaction: affective commitment and organizational tenure. Collectively these two predictors explain about 26 of the variance in job satisfaction. Although this study did not examine all the possible correlates and predictors of job satisfaction that have been identified in the organizational behavior/psychology and management literature, it nevertheless provides an empirical glimpse of the job satisfaction phenomenon among Malaysian academic librarians.